2019
DOI: 10.1038/s41598-019-39562-y
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Ppp1r15a minimises weight gain and insulin resistance during caloric excess in female mice

Abstract: Phosphorylation of the translation initiation factor eIF2α within the mediobasal hypothalamus is known to suppress food intake, but the role of the eIF2α phosphatases in regulating body weight is poorly understood. Mice deficient in active PPP1R15A, a stress-inducible eIF2α phosphatase, are healthy and more resistant to endoplasmic reticulum stress than wild type controls. We report that when female Ppp1r15a mutant mice are fed a high fat diet they gain less weight than wild type litterm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Dephosphorylation eIF2α by inducible expression of eIF2α phosphatase GADD34 in the liver can improve insulin sensitivity and reduce hepatosteatosis in mice fed a high-fat diet (HFD) 24 , and GADD34-deficient mice become obese with fatty liver by aging and HFD 25 . GADD34-deficient mice also exhibit resistance to diet-induced obesity with reduced food intake 26 , consistent with an effect of hypothalamic eIF2α phosphorylation in regulating feeding behaviors 27 . In addition, it has been reported that protein-tyrosine phosphatase 1B (PTP1B) is involved in ER stress signaling 28 and PTP1B deficiency attenuates protein synthesis in brown adipocytes by increasing PERK phosphorylation 29 .…”
Section: Introductionmentioning
confidence: 54%
“…Dephosphorylation eIF2α by inducible expression of eIF2α phosphatase GADD34 in the liver can improve insulin sensitivity and reduce hepatosteatosis in mice fed a high-fat diet (HFD) 24 , and GADD34-deficient mice become obese with fatty liver by aging and HFD 25 . GADD34-deficient mice also exhibit resistance to diet-induced obesity with reduced food intake 26 , consistent with an effect of hypothalamic eIF2α phosphorylation in regulating feeding behaviors 27 . In addition, it has been reported that protein-tyrosine phosphatase 1B (PTP1B) is involved in ER stress signaling 28 and PTP1B deficiency attenuates protein synthesis in brown adipocytes by increasing PERK phosphorylation 29 .…”
Section: Introductionmentioning
confidence: 54%
“…UBAP1 played an important role in NF‐kB signal transduction 30 . It is reported that PPP1R15A inactivation could increase insulin resistance 31 and play a proinflammatory role through endoplasmic reticulum stress 32 . The decrease of MAFF can inhibit the expression of antioxidant genes and increase the apoptosis of β cells induced by oxidative stress, 33 while the overexpression of MAFF can inhibit the transcription of NF‐E2‐related factors, which leads to immune and inflammatory reactions 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The Ppp1r15a ΔC/ΔC mouse (originally named Ppp1r15atm1Dron ) 16 had been previously backcrossed to achieve 97% C57BL/6 purity as described 5 . Experimental cohorts of male Pppr15a ΔC/ΔC and wild-type mice were generated by het × het breeding pairs unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…The unfolded protein response (UPR) has been shown to have both protective and pathological roles in development of heart failure 3 4 , and also feeding behaviour 5 6 . The rapid adaptations to diverse stimuli that induce cytosolic and ER stress, such as protein misfolding, loss of metabolites, the production of reactive oxygen species and DNA damage, are in part instigated by the phosphorylation of (eIF2α).…”
Section: Introductionmentioning
confidence: 99%